Perancangan Sistem Informasi Pergudangan - Diki Jamaludin; Djamaludin; Nurrahman, Ahmad Arif (UNISBA Press, 2024)
Abstract. CV. Patma Jaya Textile is a textile company that produces woven sarongs with a Make To Order process. This company does not yet have a warehouse information system, so the recording of incoming and outgoing goods is still done manually. This causes difficulties in managing warehouse data. This study aims to design a warehouse information system that can simplify the warehouse business process at CV. Patma Jaya Textile. The method used in this research is the Framework for Application of System Thinking (FAST) method with the stages of scope definition, problem analysis, requirement analysis, logical design, decision analysis, physical design and integration, construction and testing, installation and delivery. The result of this research is a website-based warehouse information system that can be used to record incoming and outgoing goods data, and display goods data reports. This system is designed for three users, namely admin, sales, and leadership. Based on the results of blackbox testing, the warehouse information system that has been built can function properly and according to user needs. With this information system, it is hoped that it can improve the efficiency and effectiveness of the warehouse business process at CV. Patma Jaya Textile. Abstrak. CV. Patma Jaya Textile merupakan perusahaan tekstil yang memproduksi sarung tenun dengan proses Make To Order (MTO). Perusahaan ini belum memiliki sistem informasi pergudangan, sehingga pencatatan keluar masuk barang masih dilakukan secara manual. Hal ini menyebabkan kesulitan dalam pengelolaan data pergudangan. Penelitian ini bertujuan merancang sistem informasi pergudangan yang dapat mempermudah proses bisnis pergudangan di CV. Patma Jaya Textile. Metode yang digunakan dalam penelitian ini adalah metode Framework for Application of System Thinking (FAST) dengan tahapan Scope Definition, Problem Analysis, Requirement Analysis, Logical Design, Decision Analysis, Physical Design and Integration, Construction and Testing, Installation and Delivery. Hasil penelitian ini adalah sebuah sistem informasi pergudangan berbasis website yang dapat digunakan untuk mencatat data barang masuk dan barang keluar, serta menampilkan laporan data barang. Sistem ini dirancang untuk tiga pengguna, yaitu admin, sales, dan pimpinan. Berdasarkan hasil pengujian blackbox testing, sistem informasi pergudangan yang telah dibangun dapat berfungsi dengan baik dan sesuai dengan kebutuhan pengguna. Dengan adanya sistem informasi ini, diharapkan dapat meningkatkan efisiensi dan efektivitas proses bisnis pergudangan di CV. Patma Jaya Textile.